Mimicry and the Market: Adoption of a New Organizational Form - Lee, Kyungmook; Pennings, Johannes M. (Academy of Management Journal, 2002)
This article examines the diffusion of a novel governance structure, the so-called partner-associate structure, among a population of Dutch professional services firms during the period 1925-90. An institutional change emerged out of an interaction between selection at the level of sector and imitative adoption at the firm level. We argue that market feedback regarding the novel structure fostered its legitimacy. Furthermore, the effect of market feedback is conditional upon three diffusion filters: social networks, propinquity, and strategic group membership. Diffusion as a legitimization process unfolds, therefore, at both the sectoral and the firm level of analysis.